The educational spaces for learning and their relationship with the standards of the technical norms, Tacna 2012 - Vicente Aguilar, Wilfredo Carlos (2015)
Objective: This research has the  general objective to determine the  extent to which educational spaces  for learning standards technical  standards in public educational  institutions of the city of Tacna in  2012 are related.     Method: This research is developed  in the area of the City of Tacna and  reaches a segment of the public  institutions of initial and secondary  level education, primary. For this  purpose a representative sample of  32 educational institutions, which  allowed analyzing and determining  an answer to the research question  was chosen. The research process  involved the verification of  educational and complementary  learning spaces that have public  educational institutions of the city of  Tacna in 2012. The research  process involved the administration  of technical specifications for data  collection, according standards and  indicators corresponding to each of  the educational learning spaces for  students in the city of Tacna in 2012.  The research is basic descriptive  correlational nature, which seeks to provide answers to questions associated with scohool spaces and  meeting standards of technical  standards for educational  infrastructure.     Results: The results have conditions  that are complementary teaching  and learning spaces that have public  educational institutions are low,  likewise; it is found that the level of  compliance with the standards of the  technical standards of educational  and supplementary educational  learning spaces, in public  educational institutions, are low.    Conclusion: Finally, it is determined  that supplemental educational  teaching and learning spaces have  significant relationship with the  standards of technical standards in  public educational institutions of the  city of Tacna